Maternal Personality and Child Temperamental Reactivity: Differential Susceptibility for Child Externalizing Behavioral Problems in China - Xing, Shufen; Gao, Xin; Liu, Xia; Ma, Yuanyuan; Wang, Zhengyan (Frontiers in Psychology, 2018)
It is important to identify the developmental antecedents of externalizing behavioral problems in early childhood. The current study examined the main effects of maternal personality and its interactive effects with child temperamental reactivity in predicting child externalizing behavioral problems, indicated by impulsivity and aggression. This study was composed of 70 children (Mage= 17.6 months, SD = 3.73) and their mothers. The results showed that maternal agreeableness was negatively associated with child impulsivity. Child temperamental reactivity moderated the effect of maternal conscientiousness on child impulsivity in support of the differential susceptibility model. Specifically, for highly reactive children, maternal conscientiousness was negatively associated with child impulsivity whereas this association was nonsignificant for low reactive children. Child reactivity also moderated the contribution of maternal neuroticism to child impulsivity. That is, maternal neuroticism was negatively associated with impulsivity, only for highly reactive children.